A comparative study on antioxidant properties, total phenolics, total flavonoid contents, and cytotoxic properties of marine green microalgae and diatoms - Ferdous, Umme Tamanna; Nurdin, Armania; Ismail, Saila; Shaari, Khozirah; Balia Yusof, Zetty Norhana (Elsevier B.V., 2025)
Despite having valuable and novel metabolites, the marine microalgae species are still not thoroughly investigated for their pharmaceutical and nutraceutical importance. Therefore, this study was focused on investigating the crude extracts of marine green microalgae species, Tetraselmis sp., Nannochloropsis sp., and diatoms Chaetoceros sp., and Thalassiosira sp., isolated from the Malaysian coastal region in terms of their antioxidant activity, total phenolics, total flavonoid contents and cytotoxicity against human breast cancer cells, MCF-7. Among twenty-eight crude extracts, Tetraselmis ethanol and ethyl acetate extract showed the highest amount of total phenolic (19.87 mg GAE/g), and total flavonoid content (38.58 mg QE/g of extract), respectively. From the antioxidant assays, methanol and ethyl acetate extract of Tetraselmis sp. exhibited significantly higher (p < 0.05) antioxidant activities, revealed through DPPH (54.41 ± 1.18 mg Trolox Equivalent Antioxidant Capacity or TEAC/g extract) and ABTS (41.57 ± 0.83 mg TEAC/g extract) radical scavenging activities, respectively than the rest. Ethyl acetate extract of Tetraselmis sp. also showed high ferric reducing power (113.46 ± 4.83 mg TEAC/g extract). On the contrary, methanol and ethyl acetate extract of Chaetoceros sp. showed the highest cytotoxicity towards MCF-7 and reduced the cell viability to 21.26 % and 21.56 %, respectively. The data suggest that marine diatom Chaetoceros sp. has a good cytotoxic effect on MCF-7, while marine green microalga Tetraselmis sp. has good radical scavenging and ferric reduction capabilities, warranting further investigation along with their metabolic profiling, cancer cell killing mechanism and extensive in vivo study.